Applying a science‐based systems perspective to dispel misconceptions about climate effects of forest bioenergy. Issue 8 (27th May 2021) - Cowie, Annette L.; Berndes, Göran; Bentsen, Niclas Scott; Brandão, Miguel; Cherubini, Francesco; Egnell, Gustaf; George, Brendan; Gustavsson, Leif; Hanewinkel, Marc; Harris, Zoe M.; Johnsson, Filip; Junginger, Martin; et al.
Abstract: The scientific literature contains contrasting findings about the climate effects of forest bioenergy, partly due to the wide diversity of bioenergy systems and associated contexts, but also due to differences in assessment methods. The climate effects of bioenergy must be accurately assessed to inform policy‐making, but the complexity of bioenergy systems and associated land, industry and energy systems raises challenges for assessment. We examine misconceptions about climate effects of forest bioenergy and discuss important considerations in assessing these effects and devising measures to incentivize sustainable bioenergy as a component of climate policy. The temporal and spatial system boundary and the reference (counterfactual) scenarios are key methodology choices that strongly influence results. Focussing on carbon balances of individual forest stands and comparing emissions at the point of combustion neglect system‐level interactions that influence the climate effects of forest bioenergy. We highlight the need for a systems approach, in assessing options and developing policy for forest bioenergy that: (1) considers the whole life cycle of bioenergy systems, including effects of the associated forest management and harvesting on landscape carbon balances; (2) identifies how forest bioenergy can best be deployed to support energy system transformation required to achieve climate goals; and (3) incentivizes those forest bioenergy systems that augment the mitigation value of the forest sector as a whole. Emphasis on short‐term emissions reduction targets can lead to decisions that make medium‐ to long‐term climate goals more difficult to achieve. The most important climate change mitigation measure is the transformation of energy, industry and transport systems so that fossil carbon remains underground. Narrow perspectives obscure the significant role that bioenergy can play by displacing fossil fuels now, and supporting energy system transition. Greater transparency and consistency is needed in greenhouse gas reporting and accounting related to bioenergy. Abstract : We examine misconceptions about climate effects of forest bioenergy and highlight the importance of a systems approach in assessing options and developing policy for forest bioenergy. Assessment should consider the whole bioeconomy, including the life cycle of bioenergy systems, effects on forest management and landscape carbon stocks, and effects on the energy and building sectors. Focussing on carbon balances of individual forest stands, emissions at the point of combustion and short‐term emissions reduction targets, neglects system‐level interactions and obscures the significant role that bioenergy can play by displacing fossil fuels now, and supporting energy system transformation.